CD4+ T‐cell Transcription Factors in Idiopathic REM Sleep Behavior Disorder and Parkinson's Disease. Issue 1 (10th July 2020) - De Francesco, Erika; Terzaghi, Michele; Storelli, Elisa; Magistrelli, Luca; Comi, Cristoforo; Legnaro, Massimiliano; Mauri, Marco; Marino, Franca; Versino, Maurizio; Cosentino, Marco
Abstract: Background: CD4+ T‐cell dysregulation occurs in Parkinson's disease (PD); however, it is unknown whether it contributes to PD development. The objective of this study was to investigate transcription factor gene expression in CD4+ T cells in idiopathic rapid eye movement sleep behavior disorder, the strongest risk factor for prodromal PD. Methods: Expression of transcription factors ( TBX21, STAT1, STAT3, STAT4, STAT6, RORC, GATA3, FOXP3, and NR4A2 ) was measured in CD4+ T cells from 33 polysomnographically confirmed idiopathic rapid eye movement sleep behavior disorder subjects and compared with expression in cells from matched healthy subjects and antiparkinson drugs‐naive PD patients. Results: Compared with healthy subjects, idiopathic rapid eye movement sleep behavior disorder subjects and PD patients had lower TBX21, STAT3, and STAT4, and higher FOXP3 expression. TBX21 expression discriminated healthy subjects from idiopathic rapid eye movement sleep behavior disorder subjects and PD patients, but not idiopathic rapid eye movement sleep behavior disorder subjects with PD. Conclusions: In idiopathic rapid eye movement sleep behavior disorder subjects CD4+ T cells exhibit a peculiar molecular signature strongly resembling cells from PD patients, suggesting early involvement of peripheral immunity in PD. © 2020 International Parkinson and Movement Disorder Society